Antibacterial activity of methanolic extract of Acrostichum Aureum Linn leaves against Propionibacterium acnes - Irwan Irwan; Pohan Napitupulu Nurhasanah; Amri MC Ulil; Adawiyah Rabiyatul; Akram Habibul; Nursafiah Nursafiah; Nurliza Eli (BIO Web of Conferences)
Propionibacterium acnes is the main organism that leads to acne. P. acnes belongs to a group of gram-positive bacteria. Antibiotics can be used to relieve acne, but they could lead bacteria to accumulate resistance. As a result, a safe and cost-effective treatment strategy is required. An instance is using Acrostichum aureum Linn leaves, which contain several bioactive chemicals that function as antibacterial. This study aims to identify the bioactive compounds and antibacterial activity of the methanolic extract of Acrostichum aureum Linn against Propionibacterium acnes. The study started with extraction (maceration method) with methanol solvent for 3 days, followed by phytochemical tests to identify bioactive compounds, and an antibacterial activity test using the disc diffusion method. Phytochemical tests on the methanol extract of Acrostichum aureum Linn leaves revealed five bioactive compounds consisted of alkaloids, flavonoids, tannins, steroids, and saponins. Antibacterial tests against Propionibacterium acnes exhibited no inhibition zone at concentrations of extract from 5% to 75%. However, at 100% concentration, indicating strong inhibition of P. acnes growth (diameter zone is 16 mm). Based on the research, it is conceivable to conclude that the extract has strong antibacterial activity against Propionibacterium acnes at a concentration of 100%.